METODE DRRILL DENGAN MEDIA SCRAPBOOK MENINGKATKAN KONSENTRASI BELAJAR PADA ANAK RETARDASI MENTAL - Yuni Devi Lestari; Fajar Surachmi; Sugih Wijayanti (Poltekkes Kemenkes Semarang, 2019)
Background: One disorder in children with mental retardation is an affective function disorder which is associated with concentration of mind. This is one of the symptoms of aberration in children developments, which makes it difficult for the child to concentrate. Therefore, an intervention is needed that triggers an increase in the concentration of learning, that is the drill method with scrapbook media.Purpose: This research aims to determine the effect of the drill method with scrapbook media on increasing concentration in children with mental retardation in SLB-C Widya Bhakti Semarang.Methods: This research use Pre-Experimental one group pre and post-test without control group design. The study sample was 30 mild mental retardation children in SLB-C Widya Bhakti Semarang on 4 - 12 February 2019. The sampling technique use purposive sampling and analysis of data processing use the Wilcoxon test.Results: The results of analysis using Wilcoxon test showed p value = 0.000 which proved that there were significant differences between before and after the treatment of the drill method with scrapbook media on increasing the concentration of learning in children with mental retardation in SLB-C Widya Bhakti Semarang.Conclusion: It is expected that the school can provide teaching through methods and media that are more interesting and innovative so that the learning concentration of children with mental retardation can increase.